Transformational Leadership, Work Motivation, And Organizational Commitment As Determinants Of Employee Performance: A Dual Mediation Study In The Indonesian Banking Sector - Sri Mulyani; Syaiful Amri; Muhamamd Rizki Aulia; Citra Astuti (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study investigates the transmission mechanism linking transformational leadership to employee performance through two parallel mediation pathways: work motivation and organizational commitment. Unlike prior studies that examine mediators in isolation, this research explicitly compares the relative strength of both pathways to identify the dominant psychological mechanism within the context of Indonesian banking organizations — a setting that has been consistently underrepresented in the international leadership literature. Using a cross-sectional survey design and Structural Equation Modeling (SEM-AMOS) with 385 commercial bank employees selected through stratified random sampling across five Indonesian regions, this study finds: (1) transformational leadership exerts a significant direct effect on employee performance (β = 0.421; p < 0.001); (2) work motivation mediates the relationship with an indirect effect of 0.168 (95% BCa-CI: 0.091–0.263); (3) organizational commitment mediates with an indirect effect of 0.142 (95% BCa-CI: 0.073–0.231); and (4) the pathway through work motivation is statistically stronger than the commitment pathway (contrast = 0.026; p < 0.05). The model explains R² = 0.684 of the variance in employee performance. These findings carry direct implications for the design of leadership training programs and performance management systems in banking institutions